Penerapan Metode Waspas Dalam Sistem Pendukung Keputusan Penerimaan Karyawan Baru - Syahputri (LPPM Universitas Al Washliyah Labuhanbatu, 2023)
Bumi Menara Internusa is a company engaged in the production and sale of canned food. In selecting applicants for PT. Bumi Menara Internusa usually provides several requirements or criteria to determine the ability and personality of the applicant, the result data is usually stored in an archive of applicants which must be compared one by one so that a decision is obtained. Of course this takes a long time and is less effective. Often we find employees who have just entered a company only last for a short period of time. The main reason is the wrong recruitment / acceptance of new employees. After being recruited, it turned out that this employee did not have the skills or qualifications required by the job. The process of accepting new employees is still not carried out professionally, but is carried out by means of bribery, friendship, or family relations. This is because there is no standard, systematic method for assessing the eligibility of prospective employees. The purpose of this study is to build the Waspas Method that can be accessed by operators at PT. Earth Tower Internusa. The benefits obtained are to simplify the process of evaluating employee acceptance so that the results are more precise and accurate because they are based on predetermined criteria and weights.